Caracterización morfológica, fisiológica y anatómica en los cultivares de café Bourbon y Typica en la finca “Agro Loja” de la parroquia Malacatos cantón Loja - Moncayo Herrera, Daniel Fernando (2024)
Coffee is a crop of economic, social and environmental importance at both the global and national levels; the province of Loja stands out for the production of quality coffee and high altitude. However, low productivity has been a problem to be faced in the coffee growing in Loja and the identification of varieties at the time of cultivation presents another problem for the farmer. This research was carried out at the Agro Loja farm in the parish of Malacatos in Loja canton in order to determine the morphological, physiological and anatomical characteristics of the Bourbon and Typica coffee cultivars. The research began with a coffee plantation already established for 5 years. A population sampling was used, selecting 10 plants with the best conditions for each cultivar. The morphological variables evaluated were: stem diameter, number of branches per plant, branch length, leaf length and width, leaf petiole length, number of leaves per plant, young leaf color, internode length, leaf apex angle, central axis branch insertion angle, number of fruits per branch and stipule edge length; physiological variables were chlorophyll, stomatal density, number of epidermal cells and stomatal index, and anatomical variables were anatomical leaf structure, stomata structure and conducting vessel structures. The results for the morphological characteristics both cultivars presented similar values, but in the physiological characteristics the best values were for the Bourbon cultivar and in the anatomical characteristics the best values were for the Typica cultivar. In conclusion, the anatomy of coffee plants is an indication to determine a better characterization.